Tracing the (hidden) spatialities of digital agendas: the case of ‘Digital Hungary’ - Varró, Krisztina (European Spatial Research and Policy, 2019)
Policies that aim at bringing about a digital transformation (seek to) create the conditions for particular spatial development trajectories. Yet, the understandings, explicit and implicit, of space advanced by digital agendas have remained rather underexposed to date. This paper addresses this gap by developing a Foucauldian-inspired discourse-analytical framework and applies it to the programme of ‘Digital Hungary’. It is argued that policies of digitalisation in Hungary only to a minor extent consider the spatial dimension, and their impact potentially undermines the declared aims of spatial development at different scales.